LEVERAGE, PROFITABILITY DAN KINERJA KEUANGAN: BUKTI DARI PERUSAHAAN KONSTRUKSI - Stevany Febreany (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
Global economic conditions are experiencing a slowdown and the Covid-19 pandemic will have an impact on the construction sector in terms of project continuity and raw materials including a shift or relocation of the budget to focus on handling Covid-19. The purpose of this study to determine the effect of leverage and profitability partially and simultaneously on the company's financial performance. The research method is using secondary data, quantitative analysis. The finding are leverage and profitability have a partial effect on the company's financial performance, the results in the study of leverage have a negative effect and profitability have not significant effect. Leverage and profitability have a simultaneous effect on the company's financial performance.